Antegrade repositioning of Memokath stent in malignant ureteroileal anastomotic stricture - Ng, K.L.; Nawawi, O.; Lim, B.K.; Htun, T.H.; Dublin, N.; Razack, A.H.A. (Elsevier, 2017)
Ureteric strictures are common and can be due to benign or malignant causes. Various surgical treatments can be used from minimally invasive endoscopic retrograde JJ stent insertion, balloon dilatation, ureterolithotomy, to open surgical exploration and repair. Memokath 051 stent is a metallic stent designed for long-term ureteral stenting in the management of ureteral strictures. The insertion of this device is usually a straightforward procedure performed endoscopically in a retrograde fashion via cystoscopy. However, this procedure can be difficult in complicated scenarios when the bladder has been removed with neoureteral reimplantations or high-grade strictures. Here, we report a case of Memokath stent insertion complicated by placement difficulties in a lady with ileal conduit due to previous ovarian cancer complicated by vesicovaginal fistula, who presented with malignant stricture of the ureteroileal anastomosis. We describe a simple yet effective antegrade technique to precisely reposition the malpositioned Memokath stent, along with illustrations.